2010
DOI: 10.1007/s11095-010-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy of Inhalable Levofloxacin-Loaded Polymeric Nanoparticles Against E. coli Biofilm Cells: The Effect of Antibiotic Release Profile

Abstract: The antibiotic release profile has an equally significant influence on the biofilm eradication rate as the antibiotic dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…[107] Growth inhibition of S. epidermidis biofilms due to application of triclosan-containing DPPC:PI, DPPG:PI or DPPC liposomes was evaluated and linked to the drug to lipid molar ratio's. [75] All the liposomes tested showed a certain degree of inhibition of the bacterial growth, but only for low drug to [96] lipid ratios an advantage of liposomal delivery was seen. The targeting to the biofilm was less pronounced for high drug/lipid ratios, which could explain these results.…”
Section: Non-specific Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…[107] Growth inhibition of S. epidermidis biofilms due to application of triclosan-containing DPPC:PI, DPPG:PI or DPPC liposomes was evaluated and linked to the drug to lipid molar ratio's. [75] All the liposomes tested showed a certain degree of inhibition of the bacterial growth, but only for low drug to [96] lipid ratios an advantage of liposomal delivery was seen. The targeting to the biofilm was less pronounced for high drug/lipid ratios, which could explain these results.…”
Section: Non-specific Targetingmentioning
confidence: 99%
“…This is needed to prevent the increase in antibiotic tolerance of the surviving biofilm cells. [96] In a time-kill biofilm susceptibility test which was conducted over five days, in vivo conditions of drug removal were simulated by diluting the solution twofold every 24 hours. This test takes into account the effect of biofilm age and could reveal if the susceptibility of the biofilm is changed during a prolonged antibiotic exposure.…”
Section: Controlled Releasementioning
confidence: 99%
“…Turos et al 14 showed polyacrylate nanoantibiotics associated with penicillin against methicillin-resistant S. aureus (MRSA), while, in this study, 64 µg⋅mL -1 minimum inhibitory concentration was also observed against MRSA. 14,15 Another study performed by Cheow et al 38 showed levofloxacin-loaded polymeric nanoparticles with 0.03 and 0.15 µg⋅mL -1 minimum inhibitory concentration and minimum biofilm inhibitory concentration against E. coli. 38 Furthermore, no hemolytic activities for tested samples were observed ( Figure S4), suggesting no cytotoxic activity against these cells, as previously observed by Nassar et al 28 These results demonstrated that nanoformulated clavanin here studied could be a suitable candidate for pharmaceutical applications.…”
Section: In Vitro Bioassaysmentioning
confidence: 99%
“…14,15 Another study performed by Cheow et al 38 showed levofloxacin-loaded polymeric nanoparticles with 0.03 and 0.15 µg⋅mL -1 minimum inhibitory concentration and minimum biofilm inhibitory concentration against E. coli. 38 Furthermore, no hemolytic activities for tested samples were observed ( Figure S4), suggesting no cytotoxic activity against these cells, as previously observed by Nassar et al 28 These results demonstrated that nanoformulated clavanin here studied could be a suitable candidate for pharmaceutical applications. This experiment associated with survival assays displayed in Figure 3 allows peptide viability to be inferred.…”
Section: In Vitro Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation